A meta-analysis of gabapentin and multimodal analgesics - Doleman, Brett (2017)
Multimodal analgesia has been proposed as a useful strategy to reduce postoperative pain while decreasing opioid consumption and thus opioid adverse events. Gabapentin is one such agent although previous results have been heterogeneous. This thesis aimed to review randomised controlled trials of gabapentin for reducing pain, opioid adverse effects and the haemodynamic response to intubation while attempted to predict clinical effectiveness from these trials using meta-regression. Extending this principle, we evaluated other multimodal analgesic agents to identify whether heterogeneity could be explained by various clinical and methodological covariates.